Mission Is Not Only about Preaching - Niyonsaba, Françoise (International review of mission, 2018)
This article reflects on the mission of the church and how it is done. This article intends to show that the church is called not only to preach, but also to exercise diakonia and empower those at the margins who are also part of the body of Christ. Discipleship, the Great Commission Jesus entrusted to his disciples and the church, is not only to speak what the Bible says or to evangelize, but also to practise what the Bible says and to serve people in need. The church as the body of Christ is composed of all people from all nations, races, and tribes, weak and strong, rich and poor, and they all have equal rights. The church is called to participate in the mission of God by serving all creation. For that reason, the church should raise the voice of the voiceless, use its prophetic voice in times of violence and injustice, and advocate for peace and justice. Most of the time the church seems to be like the Priest and the Levite who neglected their colleague while the Samaritan saved him (Luke 10:29-35). The church seems not to see the injustice and oppression happening today and remains silent. But, again, it cannot work if injustice and oppression remain within the church. To spread peace and justice in the world, the church should first uproot the injustice and oppression within itself so that people see its fruits and come to Christ.